166. Deformable Image Registration on Head and Neck radiotherapy patient: Comparison of automatic mapping and manual countouring. (December 2018) - Giostra, A.; Gino, E.; Moro, G. Lo; Cutaia, C.; Pasquino, M.; Nassisi, D.; Redda, M.G. Ruo; Stasi, M.
Abstract: Purpose: Deformable Registration (DR) is necessary for dose accumulation process and it could be very useful for contour propagation from planning CT ( CT 0 ) to a CT or CBCT acquired during the radiotherapy treatment ( CT n, CBCT n ) . The purpose of this study is to evaluate the goodness of contours mapped by TPS RayStation ( V ROI-map ) in comparison with the ROIs countered by physicians ( V ROI-ph ) and to test the reliability of automatic mapping in terms of dose calculation. Methods. Results: Three methodologies of DR were evaluated applying automatic contour propagation on 9 head and neck patients: hybrid without control-ROIs, hybrid with spinal cord as control ROI, hybrid with spinal cord and CTVs as control-ROIs. The volumes of GTVs, CTVs and parotid glands were mapped from CT to CT n and CBCT n . The approved plan was calculated on CT n and CBTC n using both groups of ROIs ( V ROI-map and V ROI-ph ) and collecting doses: D mean, D 95 %, D max . The t-test was used to compare ranges of volumes and dose coverage. Conclusions: The volumes of ROIs obtained during radiotherapy treatment by applying automatic DRs and volumes manually corrected by physician after a rigid copy from CT 0 are summarized in table. On these sets of ROIs, the approved treatment plan was calculated. By applying the t-test on set of volumes no significant difference was found.